2020
DOI: 10.1016/j.xcrm.2020.100152
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Motivational Deficits in Pre-manifest Huntington’s Disease

Abstract: Summary Motivation is characterized by a willingness to overcome both cognitive and physical effort costs. Impairments in motivation are common in striatal disorders, such as Huntington’s disease (HD), but whether these impairments are isolated to particular domains of behavior is controversial. We ask whether HD differentially affects the willingness of individuals to overcome cognitive versus physical effort. We tested 20 individuals with pre-manifest HD and compared their behavior to 20 controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 79 publications
8
33
0
Order By: Relevance
“…To derive the best estimates of each individual’s willingness to invest effort, we fit participants’ choices to three functions that are commonly used to model effort discounting—linear, parabolic, and hyperbolic. These model comparisons revealed that participants’ choices were best fit by a parabolic pattern of effort discounting (AIC: parabolic = 4544, linear = 4787, hyperbolic = 5329; BIC: parabolic = 5042, linear = 5285, hyperbolic = 5826), which is consistent with previous work 36 , 52 , 53 , 64 , 69 , 70 . We then extracted the k -values for each participant from the winning model, and correlated them with ratings on the apathy and fatigue inventories.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…To derive the best estimates of each individual’s willingness to invest effort, we fit participants’ choices to three functions that are commonly used to model effort discounting—linear, parabolic, and hyperbolic. These model comparisons revealed that participants’ choices were best fit by a parabolic pattern of effort discounting (AIC: parabolic = 4544, linear = 4787, hyperbolic = 5329; BIC: parabolic = 5042, linear = 5285, hyperbolic = 5826), which is consistent with previous work 36 , 52 , 53 , 64 , 69 , 70 . We then extracted the k -values for each participant from the winning model, and correlated them with ratings on the apathy and fatigue inventories.…”
Section: Resultssupporting
confidence: 89%
“…This was a purposeful element of our design to eliminate the possibility of choices being confounded by the accumulation of short-term fatigue, which is particularly important given the unclear relationship between fatigue as a trait, and shorter term fatiguability 15 , 56 , 57 . We note that previous studies have demonstrated the sensitivity of hypothetical decisions to quantifying effort discounting 23 , 36 , 52 , 58 , 59 and other reward-based behaviour 58 , 60 63 . The choice phase was presented in Presentation software (Neurobehavioral Systems), and participants made choices using the left and right arrow keys.…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…These findings also leave open further questions about whether subjective changes in reward value and probability influence the value of non-instrumental information about those rewards. One example of this is effort discounting, in which the value of a reward is reduced when it is earned through effortful, as opposed to non-effortful means 51 55 . While evidence for the IOC has not been demonstrated in neural indices of reward 31 , the modulation of reward signals has been demonstrated in tasks requiring effort 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%